Comprehensive evaluation and spatial-temporal differences analysis of China’s inter-provincial doing business environment based on Entropy-CoCoSo method - Zhu, Yanmin; Zeng, Shouzhen; Lin, Zhisen; Ullah, Kifayat (Frontiers in Environmental Science, 2023)
Introduction: The Doing Business environment affects the operation of enterprises in the region and exerts an important impact on economic development, taxation, and employment. Methods: According to the characteristics of large differences in the level of economic development between provinces in China, this study builds a set of scientific and reasonable evaluation index systems of inter-provincial Doing Business environment, including five first-level indicators and 11 second-level indicators. Moreover, this study constructs a comprehensive evaluation model based on the Entropy-CoCoSo framework and explores its application in China’s inter-provincial Doing Business environment evaluation. Results: Based on China’s provincial panel data from 2007 to 2020, the research found that the Doing Business environment of each province has generally improved in recent years, but the inter-provincial differences are more prominent. The western provinces have obvious late-mover advantages. Discussion: Finally, we put forward several targeted suggestions, providing a powerful reference for optimizing China’s Doing Business environment and promoting high-quality economic development.